Acupuncture therapy for poststroke spastic hemiplegia: A systematic review and meta-analysis of randomized controlled trials. (August 2020) - Fan, Wenjuan; Kuang, Xu; Hu, Jiawei; Chen, Xiaowei; Yi, Wei; Lu, Liming; Xu, Nenggui; Wang, Lin
Abstract: Background: Hemiplegia after stroke is one of the main dysfunctions in stroke patients. Acupuncture had been widely used for poststroke spastic hemiplegia (PSSH), but the efficiency was unclear. This study aimed to examine the efficiency and safety of acupuncture for individuals with PSSH. Methods: We searched nine databases from their inception to 27 th July 2019. Randomized controlled trials (RCTs) of acupuncture for the treatment of PSSH met the screening criteria. The quality of methodology was evaluated by Cochrane's risk of bias tool. RevMan 5.3 was used to perform the meta-analysis. The primary outcome was the Fugl-Myer Assessment (FMA) score, and the secondary outcomes were the Ashworth Scale for Spasticity (ASS) and Barthel Index (BI) scores. To evaluated the safety of acupuncture therapy, researchers scanned the full text to collect adverse events. Results: Researchers retrieved 2452 articles in total, after screening, thirty-eight studies with 2628 participants of were included. In this meta-analysis, twenty-seven trials revealed that acupuncture therapy was associated with an increase in FMA scores compared with rehabilitation training (RT) (MD: 8.43, 95% CI, 6.57 to 10.28, p < 0.00001, I 2 = 75%). According to the analysis of subgroup of interventions, ten trials showed that manual acupuncture (MA) plus RT was associated with an increase in FMA compared with RT (MD: 10.84, 95% CI, 9.29 to 13.29, p < 0.00001, I 2 = 24%), three trials showed that electroacupuncture (EA) plus RT was associated with an improvement in FMA compared with RT (MD: 9.44, 95% CI, 1.00 to 17.88, p = 0.03, I 2 = 81%), twelve trials showed that MA was associated with an increase in FMA compared with RT (MD: 5.48, 95% CI, 2.07 to 8.89, p = 0.002, I 2 = 74%), and one trials showed that EA was associated with an improvement in FMA compared with RT (MD: 11.35, 95% CI, 5.03 to 17.67, p = 0.0004). According to the analysis of subgroup of treatment duration, four trials used acupuncture therapy for more than 1 month, revealed that acupuncture therapy was associated with an increase in FMA scores compared with RT (MD: 9.24, 95% CI, 0.42 to 18.06, p = 0.04, I 2 = 93%). Thirty-two trials used acupuncture therapy for less than or equal to 1 month, revealed that acupuncture therapy was associated with an increase in FMA scores compared with RT (MD: 8.32, 95% CI, 6.56 to 10.09, p < 0.00001, I 2 = 61%). Six trials indicated that acupuncture therapy was better than RT in terms of the ASS (MD: 0.46, 95% CI, −0.65 to −0.27, p < 0.00001, I 2 = 67%), twenty-four trials indicated that acupuncture therapy was better than RT in terms of the BI scores (MD: 8.32, 95% CI, 5.30 to 11.35, p < 0.00001, I 2 = 88%). In general, the methodologies of the RCTs were of poor quality. Two RCTs reported no adverse events, one trial reported five adverse events without severe influence, others did not mention. Conclusions: This review discovered that acupuncture might be a safe and effective adjuvant therapy for individuals with PSSH. Nevertheless, there were methodological limitations in the included RCTs, and well-designed and large-scale studies should be carried out to confirm our results.